Assessment of Radiation Hazards Parameters Associated with Natural Radionuclides in Granite Used in El-Beida, Libya (Al-Mukhtar Journal of Basic Sciences, 2025)
Using a gamma ray1spectrometer equipped with an NaI(Tl) scintillation detector, the levels of natural1radionuclides in granite samples used as building materials that were collected from local markets in El-Beida, Libya, were investigated. For 226Ra, 238U, 232Th, and 40K, the respective activity concentrations range from 40.96±1.47 to 205.48±0.13 Bqkg⁻¹, 52.25 ±1.53 to 182.65 ±2.36 Bqkg⁻¹, 49.72 ±1.17 to144.32 ±1.51 Bqkg⁻¹ and 49.41±1.18 to 271.75 ±2.74 Bqkg⁻¹. All granite samples had radioactive levels that exceeded recommended1world limits for 226Ra, 238U, and 232Th (UNSCEAR), according to the data. But the activity concentration levels in all granite samples were 40K, below the UNSCEAR worldwide1recommended values. Natural1radionuclide-related radiological1hazard parameters were evaluated. The radiological hazard parameters associated with natural1radionuclides were evaluated. The results were compared to other studies done elsewhere in the world and world-recommended values. Consciously, some parameters are lower or inside recommended limits, but others showed values higher than internationally1accepted limits. The results indicate that for most studied granite samples, the radiation1hazards from terrestrial radionuclides are not significant for use as building materials .